Cardiac Autonomic Modulation in Response to Muscle Fatigue and Sex Differences During Consecutive Competition Periods in Young Swimmers: A Longitudinal Study - Castillo-Aguilar, Matías; Valdés-Badilla, Pablo; Herrera-Valenzuela, Tomás; Guzmán-Muñoz, Eduardo; Delgado-Floody, Pedro; Andrade, David Cristóbal; Moraes, Michele M.; Arantes, Rosa M. E.; Núñez-Espinosa, Cristian (Frontiers in Physiology, 2021)
Objective: To study the differences in cardiac autonomic modulation in response to muscle fatigue caused by high-intensity exercise during two consecutive competition periods in young swimmers. Methods: Twenty-six competitive swimmers, selected by their training volume, were separated in two groups, females (n=12 [46%], age: 13.5 ± 1.4 years) and males (n=14 [54%], age: 13.9 ± 1.7 years), aged between 10 and 16 years, were evaluated five times as follow: i) 21 days before the first competition (t-0); ii) two days before (t-1; t-3); and iii) two days after (t-2; t-4) of the first and second competitions. Morphological measurements (body mass, percentage of total body fat and height), blood pressure, power, and resting heart rate variability (RR with Polar band) were recorded before and after Wingate test at each time. Results: Body fat was higher in females compared to males. No differences were found in other morphological parameters. An intra-subject analysis grouped by sex in cardiovascular parameters shows longitudinal variations in systolic pressure and mean pressure among females. Females depicted higher, very low frequency (intrinsically generated by the heart and associated with emotional stress) after physical fatigue compared to males at t-1. Further, before the competition, the high frequency component of HRV (parasympathetic drive) was higher in males than females at t-0 and t-4. Conclusion: Our data revealed that males displayed greater parasympathetic reactivity after an anaerobic muscle fatigue test during their competition periods. Females had a less cardiac autonomic modulation when comparing the pre-post Wingate test after two consecutive competition.